1982
DOI: 10.1016/0010-0285(82)90007-x
|View full text |Cite
|
Sign up to set email alerts
|

Scene perception: Detecting and judging objects undergoing relational violations

Abstract: Five classes of relations between an object and its setting can characterize the organization of objects into real-world scenes. The relations are (1) Interposition (objects interrupt their background), (2) Support (objects tend to rest on surfaces), (3) Probability (objects tend to be found in some scenes but not others), (4) Position (given an object is probable in a scene, it often is found in some positions and not others), and (5) familiar Size (objects have a limited set of size relations with other obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
868
10
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 974 publications
(932 citation statements)
references
References 16 publications
46
868
10
8
Order By: Relevance
“…Graf et al suggested that the first object in the sequence adjusts the orientation of an abstract reference frame in which the second object is initially processed. However, the preceding context may also provide semantic and structural information that could facilitate the recognition of the object (Bar, 2004;Biederman et al, 1982) in addition to orientation priming. Bar (2004) recently proposed a physiologically motivated model of object recognition in which he suggested that the scene context may facilitate the initial processing of the objectfor example, by limiting the search space during object recognition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graf et al suggested that the first object in the sequence adjusts the orientation of an abstract reference frame in which the second object is initially processed. However, the preceding context may also provide semantic and structural information that could facilitate the recognition of the object (Bar, 2004;Biederman et al, 1982) in addition to orientation priming. Bar (2004) recently proposed a physiologically motivated model of object recognition in which he suggested that the scene context may facilitate the initial processing of the objectfor example, by limiting the search space during object recognition.…”
Section: Methodsmentioning
confidence: 99%
“…Hollingworth and Henderson (1998), however, attributed the results of Biederman et al (1982) to response bias. These authors did not find a congruency advantage when they controlled for bias and concluded that object identification is isolated from semantic information about the scene context.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When scenes are used, it is to assess the role of perceptual context in object recognition (e.g., Aginski & Tarr, 2000;Biederman et al, 1982;Boyce, Pollatsek, & Rayner, 1989;Delorme, Fabre-Thorpe, Richard, Fize, & Thorpe, 1998;Hollingworth & Henderson, 1998;Intraub, 1997;Sanocki, Bowyer, Heath, & Sarkar, 1998). For example, Delorme et al (1998) presented humans and monkeys 400 pictures of food and animals in their natural background scene contexts.…”
Section: Luminance Color and Recognitionmentioning
confidence: 99%
“…However, this depiction does not account for all situations of recognition. Scenes are often recognized very quickly, in a single glance-in fact, as fast as a single component object (Biederman, Mezzanotte, & Rabinowitz, 1982;Friedman, 1979;Intraub, 1997;Potter, 1976). Under these conditions, it has been shown that visual information could mediate scene recognition without the prior and necessary recognition of component objects (Schyns & Oliva, 1994).…”
mentioning
confidence: 99%